Four cases of pneumomediastinum: Case Report. Issue 4 (December 2015) - Aujayeb, Avinash; Miller, Jonathan; Weatherhead, Mark; Cooper, David
Pneumomediastinum or mediastinal emphysema is defined as the presence of air in the mediastinum, the central compartment of the thoracic cavity that contains the heart and its vessels, the oesophagus, trachea, vagus and phrenic nerves, and thymus, among other organs. There are no concrete epidemiological data but case series point to an approximate incidence of one in 7000 to one to 45 000 hospital admissions [1–3], with a predilection for young males [2]. Pneumomediastinum is an uncommon clinical entity that can have disastrous consequences http://ow.ly/UtYYh